Dynamics of classified forests in the urban district of Bobo-Dioulasso in Burkina Faso - Francoise, Valea; Karambiri, Bienvenue Lawankilea Chantal Noumpoa; Sanou, Korotimi (Penerbit Universiti Kebangsaan Malaysia, 2024)
In Burkina Faso, the natural environment is subject to continuous degradation of its forest resources. If the phenomenon is recurrent in rural areas, urban forests are considered to be land reserves that are exposed to exploitation rather than to the preservation of the environment and its biodiversity. To remedy this, Burkina Faso developed a policy for the development of classified forests in 1981, to guarantee balanced exploitation of its forest resources. Such initiatives, combined with the decentralization of power to local authorities over the past three decades, require a closer look at the development of classified forests in the context of climatic variability. The classified forests of Dinderesso and Kua, located in the urban commune of Bobo-Dioulasso, are illustrative cases. The objective of this study is to analyze the factors that contribute to forest degradation and the management practices adopted by stakeholders and community groups. A diachronic study was carried out on the dynamics of plant cover in the classified forests of Dinderesso and Kua in 1988, 2003 and 2018, coupled with an analysis of climatic parameters (1988-2018). The results show that the agricultural production system, the cutting of wood for energy, pastoral practices, and water stress linked to rising temperatures have a negative impact on the development of peri-urban forests. A diachronic analysis of land use units reveals an improvement in forest resources thanks to participatory management by local people, supported by development activities carried out by projects.